2018
DOI: 10.3892/mmr.2018.9525
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella‑induced miR‑155 enhances necroptotic death in macrophage cells via targeting RIP1/3

Abstract: Salmonella enterica serovar Typhimurium (hereafter referred to as Salmonella), a virulent pathogen, is known to induce host-cell death. Using reverse transcription-quantitative polymerase chain reaction, a 28-fold increase of microRNA (miR)-155 expression in RAW 264.7 macrophages was observed following infection with Salmonella for 24 h. This miR-155 upregulation increased macrophage cell death by up to 40% in 48 h following infection. Western blot analysis revealed that receptor interacting protein 1 (RIP1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…Other explorations of necroptosis in the context of S . Typhimurium infection involved the use of qRT-PCR techniques to assess the expression of micro RNAs (miRNAs) induced by infection in RAW264.7 cells (78). A highly upregulated miRNA, miR-155, mediated cytotoxicity levels similar to S .…”
Section: Salmonella Infection and Necroptotic Cell Deathmentioning
confidence: 99%
See 3 more Smart Citations
“…Other explorations of necroptosis in the context of S . Typhimurium infection involved the use of qRT-PCR techniques to assess the expression of micro RNAs (miRNAs) induced by infection in RAW264.7 cells (78). A highly upregulated miRNA, miR-155, mediated cytotoxicity levels similar to S .…”
Section: Salmonella Infection and Necroptotic Cell Deathmentioning
confidence: 99%
“…A highly upregulated miRNA, miR-155, mediated cytotoxicity levels similar to S . Typhimurium-infected cells when transfected into RAW264.7s (78). Further in vitro transfections indicated that miR-155 induced RIPK1 and RIPK3 phosphorylation (indicative of necroptosis) by 18 h post-treatment, as well as cleavage of poly (ADP-ribose) polymerase-1 (PARP-1) in a similar manner to S .…”
Section: Salmonella Infection and Necroptotic Cell Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting necroptotic cell death facilitates macrophage elimination, leading to compromised pathogen control. Alternatively, Ro et al [ 118 ] reported that microRNA (miR)-155 upregulation following S. Typhimurium infection drives necroptotic macrophage death. Transfection of miR-155 in vitro induces RIPK1 and RIPK3 activation and subsequent necroptosis, which is partly inhibited following Nec-1 treatment.…”
Section: Introductionmentioning
confidence: 99%